Developing perceived self-efficacy in later life through poetry writing. An analysis of a U3A poetry group of older Australians. Issue 2 (3rd March 2020) - Creely, Edwin; Southcott, Jane
ABSTRACT: A change-of-life issue for older people is finding ways to engage meaningfully and be creative. Sustaining a sense of self-efficacy in one's abilities to be productive is vital for wellbeing. Our research explored the perceived self-efficacy developed in an Australian University of the Third Age poetry class. We gathered data from one class session through observation, a focus group and paired interviews. Transcribed data identified participants' voices, and common themes were noted. We use Bandura's idea of perceived self-efficacy, through examining mastery experiences, modelling, social persuasion and a positive learning climate to understand the data. These sources of self-efficacy were pivotal for participants' positive self-efficacy. We offer this example of how older people can achieve mastery in a new field of creative endeavour at a time in their life-course often positioned as diminishing. In doing so, we challenge conventional understandings of ageing.